On the Origin of the Improved Ruthenium Stability in RuO2–IrO2 Mixed Oxides. Issue 11 (1st January 2016) - Kasian, Olga; Geiger, Simon; Stock, Philipp; Polymeros, George; Breitbach, Benjamin; Savan, Alan; Ludwig, Alfred; Cherevko, Serhiy; Mayrhofer, Karl J. J.
Abstract : High oxygen evolution reaction activity of ruthenium and long term stability of iridium in acidic electrolytes make their mixed oxides attractive candidates for utilization as anodes in water electrolyzers. Indeed, such materials were addressed in numerous previous studies. The application of a scanning flow cell connected to an inductively coupled plasma mass spectrometer allowed us now to examine the stability and activity toward oxygen evolution reaction of such mixed oxides in parallel. The whole composition range of Ir–Ru mixtures has been covered in a thin film material library. In the whole composition range the rate of Ru dissolution is observed to be much higher than that of Ir. Eventually, due to the loss of Ru, the activity of the mixed oxides approaches the value corresponding to pure IrO2 . Interestingly, the loss of only a few percent of a monolayer in Ru surface concentration results in a significant drop in activity. Several explanations of this phenomenon are discussed. It is concluded that the herein observed stability of mixed Ir–Ru oxide systems is most likely a result of high corrosion resistance of the iridium component, but not due to an alteration of the material's electronic structure.